DETERMINAN PEMBANGUNAN EKONOMI DAN PEMBANGUNAN MANUSIA DI SUMATERA - Nisrina Atikah (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2023)
This paper aimed to analyze the economic development including its macroeconomic variables in Sumatra during 2014-2020 by using simultaneous equation model with panel data. The results showed the existence of two-way relationship between economic and human development in Sumatera. The government spending and net export have significant and positive impact on economic growth. Household consumption and mean years schooling have significant and positive impact on Human Development Index in Sumatera. In brief, two determinants of economic growth of Sumatera are government spending and net export. Meanwhile, household consumption and mean years schooling have the indirect effect on economic growth. Keywords: economic development, human development, growth’s determinants